PENGURUSAN PEMELIHARAAN SENI TRADISI SENJATA TERABAI KAUM IBAN DI SARAWAK - ALEXANDER, GEORGE ROBIN (2016)
This research is concerned with the management of neglected preservation of traditional arts weapon or shield the Iban in Sarawak. Whereas the objective of this research is on the management of neglected preservation of heritage. Art weapons tradition neglected Iban in Sarawak is one of the legacy that is still inherited by Iban from ancient times up until this point. Thus, data and research information obtained by researchers after conducting several methods such as observation and interviewing people selected informants and on-site investigations have been. As a result of this investigation, it has been shown that a significant change in terms of functionality neglected in the past and now. As previously neglected tradition weapon is used as a means of self-protection and it is also used as ornaments. Thus, changes in terms of material and motifs that are used to generate neglected at this point also shows that it is experiencing dramatic changes because of abandoned Iban tradition at this point have been used as a cultural product commercialization.